P-377 Does C-Section history affect the live birth outcomes after IVF in case of frozen embryo transfers?. (30th June 2022) - Bayram, A; Elkhatib, I; Abdala, A; El Damen, A; Melado Vidales, L; Lawrenz, B; Fatemi, H
Abstract: Study question: Do previous Caesarean section deliveries (CD) affect reproductive outcomes in case of frozen embryo transfers (FET), including live births (LB), after IVF or ICSI? Summary answer: Previous CD does not impair LBR after IVF when cycle segmentation is performed and intracavitary fluid (ICF) is eliminated prior frozen embryo transfer. What is known already: Successful implantation requires not only a receptive endometrium, but also the process of 'apposition' and 'attachment' of the embryo to the endometrial surface. This process could be severely disturbed by previous CD and data are contradictory regarding its impact on ART outcome. Former CD might not only increase the difficulty of the ET-procedure, but might also lead to the presence of ICF. Therefore, special attention has to be paid to exclude fluid accumulation during preparation for FET. When ICF is excluded, the reproductive outcomes of FET cycles appear to be uncompromised, regardless of the previous delivery mode. Study design, size, duration: This single center retrospective cohort study included a total of 412 single/double euploid FET cycles between March 2017 and October 2019. Trophectoderm biopsy samples were subjected to Next Generation Sequencing to diagnose the ploidy state. Vitrification and warming were performed using the Cryotop method (Kitazato, Biopharma). No embryo transfer was performed when ICF was visible during the endometrial preparation for FET. Participants/materials, setting, methods: Patients with secondary infertility, having at least one euploid embryo after a previous IVF/ICSI-cycle with embryo vitrification, undergoing FET, were included. Clinical pregnancy rate (CPR), early pregnancy loss (EPL) and LBR were evaluated in patients after CD and after vaginal delivery (VD). Main results and the role of chance: Patients in the CD group were significantly older than in the VD group (35.02±4.62 vs 34.11±5.03 years, respectively) (p = 0.028). FET was performed in a Natural cycle (NC) (n = 82, 46.86%) or in a Hormonal replacement therapy (HRT) cycle (n = 93, 53.14%) in CD group versus NC (n = 77, 32.49%) or HRT cycle (n = 160, 67.51%) in VD group (p = 0.003). Patient characteristics (AMH, BMI, duration of infertility, presence of intrauterine abnormalities, endometrial thickness, embryo quality, presence of blood on the transfer catheter and number of SETs/DETs) were similar between groups. Embryo transfer difficulty and the presence of mucus on the transfer catheter were significantly higher in CD group versus VD group (p = 0.040, p=0.004, respectively). Pregnancy outcomes CPR (61.71% vs 63.71%), EPL (12% vs 12%) and LBR (60% vs 60.34%) did not differ statistically between the CD and VD groups. In the multivariate regression model with embryo-quality, cycle-regimen, ET-difficulty, presence of blood/mucus, age, AMH, number of transferred embryos, only embryo quality remained significantly associated with LBR in CD-group (p = 0.001). In VD-group, cycle regimen was also significant parameter besides embryo quality (p = 0.001, p = 0.001 respectively). When CD and VD groups are categorized in terms of cycle regimen, CP and LBR were similar (p = 0.828/p=0.618 in HRT; p = 0.826/p=0.150 in NC). Limitations, reasons for caution: This study is limited to its retrospective design and the fact that no distinction existed between patients with one or several previous CDs. Furthermore, this analysis is limited to patients, for whom ICF was excluded prior to ET. Wider implications of the findings: This study confirmed that in patients after CD, the chance for CP and LBR is not compromised, when ICF is excluded during the endometrial preparation for FET. The existence of C-section scar may increase the ET-difficulty and the presence of the mucus on the transfer catheter. Trial registration number: NA